Analysts' Forecast Accuracy in Germany: The Effect of Different Accounting Principles and Changes of Accounting Principles - Jürgen Ernstberger; Simon Krotter; Christian Stadler (BuR - Business Research, 2008)
This paper assesses the influence of an adoption of IAS/IFRS or US GAAP on the financial analysts forecast accuracy in a homogenous institutional framework. Our findings suggest that the forecast accuracy is higher for estimates based on IFRS or US GAAP data than for forecasts based on German GAAP data. Moreover, in the year of switching from German GAAP to US GAAP the forecast accuracy is lower than in other years. The paper contributes to prior research by providing evidence about the usefulness of international accounting data and about the adoption effects of a change to such accounting principles.
urn:nbn:de:0009-20-13914
Keywords: 650; accounting; adoption effect; analysts; analysts forecast accuracy; financial analysts; German GAAP; Germany; HGB; IAS; IFRS; IFRS adoption; learning effect; US GAAP; Finanzanalyse; Prognoseverfahren; IFRS; Bilanzierungsgrundsätze; Bilanzielle Bewertung; Deutschland